Концепція анализу "конфліктності" елементів системи орбітальних тіл - Labutkina, T. V.; Larin, V. O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A method of time-efficient forecasts of mechanical "conflict" (collision) for elements of a system of orbital bodies is represented. A concept of prediction of possible "conflict" regions in near-earth space is worked out and characteristics of danger levels of the regions are proposed.